Inefficacy of Immunosuppressive Therapy for Severe Aplastic Anemia Progressing From Non-SAA: Improved Outcome After Allogeneic Hematopoietic Stem Cell Transplantation - Liu, Limin; Zhao, Xin; Miao, Miao; Zhang, Yanming; Jiao, Wenjing; Lei, Meiqing; Zhou, Huifen; Wang, Qingyuan; Cai, Yifeng; Zhao, Liyun; Shangguan, Xiaohui; Liu, Zefa; et al. (Frontiers in Oncology, 2021)
We retrospectively compared 232 severe aplastic anemia (SAA) cases that had met the criteria for SAA at the time of diagnosis (group A) with 229 SAA that had progressed from non-SAA (NSAA) (group B), both undergoing first-line immunosuppressive therapy (IST). Additionally, group B was compared with 147 SAA that had progressed from NSAA and who had been treated by allogeneic haematopoietic stem cell transplantation (allo-HSCT) (group C) between June 2002 and December 2019. Six months after treatment, the rate of overall response and the fraction of patients who had achieved normal blood values in group A was higher than in group B (65.24% vs. 40.54%, P < 0.0001; 23.33% vs. 2.25%, P < 0.0001); the same was true for group C (92.50% vs. 2.25%, P < 0.0001). The rate of relapse in group B was higher than in group C (P < 0.0001), but there were no differences in treatment-related mortality and secondary clonal disease (P > 0.05). There were no differences in estimated 5-year overall survival between groups A and B (83.8% ± 2.6% vs. 85.8% ± 2.6%, P = 0.837), or between B and C (85.8% ± 2.6% vs. 77.9% ± 3.4%, P = 0.051). The estimated 5-year failure-free survival in groups A and C was higher than for group B (57.1% ± 3.3% vs. 39.7% ± 3.4%, P < 0.001; 76.7% ± 3.5%, 39.7% ± 3.4%, P < 0.0001). These results indicate that IST is less effective in SAA progressing from non-SAA but allo-HSCT can improve outcomes.